TEORI KREDIBILITAS : ESTIMASI MORRI -VAN SLYKE - Sidi (NIM : 28598017), Pramono
Abstract : This research is a research on credibility theory, which is an experience rating technique to determine insurance premiums for more or less heterogenous contracts. Ten territories are chosen for this research of which the object is a group of automobiles (in this case all kinds of automobiles) in each territory. The differential claim rates and the differential number of claims are estimated for each individual territory to the overall claims of the ten territories. Procedure originally developed by Morris - Van Slyke is used to obtain the insurance value. In particular, data of the 1990 and 1991 differential claim rates are used to predicial the 1992 differential claim rate using the normal-normal combination and data of the 1990 and 1991 differential of the number of claims are used to predich the 1992 differential of the number of claims using the Poisson - Gamma combination both kinds of predictinit are done for each of the ten territories. The result shavs that the Morris - Van Slyke estimator is a better compared to the full credibility as well as the zero credibility estimator. By using a measure of closeness, the following results are obtained. (1) For predicting claim rates, the Morris - Van Slyke estimator, using the James - Stein corrections factor, is a better compared to the full credibility as well as the zero credibility estimator. (2) For predicting the number of claims, the Morris - Van Slyke estimator, without using the James - Stein correction factor, is a better compared to the full credibility as well as the zero credibility estimator.